Konsep Diri Pada Remaja Otaku Anime - Putra, Bagas Reffi Hernanda Putra; Khasan, Mohammad (Universitas Muhammadiyah Sorong, 2024)
Otaku are young people, both male and female, usually between the ages of 15 to 29, and when they reach adulthood, they remain enthusiastic about cartoons that are mostly intended for children. The purpose of this study is to analyze the factors of self-concept factors in anime otaku teenagers. This research uses a qualitative method with a phenomenological approach. The data collection technique uses observation and interview methods to anime otaku teenagers. While the data analysis method uses coding and credibility testing using peer triangulation. The results showed that Informant I explained how anime community members provide a significant positive influence, by creating a sense of connectedness and solidarity through recommendations and support amidst differences in interests. Meanwhile, Informant II highlighted the role of online communities, such as on Facebook and Discord, in strengthening her identity as an anime fan. Informant III emphasized her active role as an anime fan who not only enjoys entertainment but also understands Japanese culture. She seeks to change negative stereotypes of anime fans through her participation in positive communities. Similarly, Informant I focuses more on social support and self-discovery, Informant II on self-discovery and courage, while Informant III on cultural understanding and active role in the community.